2017
DOI: 10.4172/2155-6180.1000348
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Risk Factors Associated with Helicobacter pylori Infection in Lahore, Pakistan

Abstract: Citation: Ali A, Ahmad MR, Iqbal Z, Basit A (2017) Identification of the Risk Factors Associated with Helicobacter pylori Infection in Lahore, Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The risk factors for H. pylori infection are sex (10) , age (11,12) , smoking (13) , alcohol consumption (14) , contaminated food (12) , untreated water intake (5) , family size (15) , bed sharing (16) , poor living conditions in childhood (17) , educational (13) and socioeconomic level (18) , hygiene (19) , and family medical history of gastric disease (11) .…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors for H. pylori infection are sex (10) , age (11,12) , smoking (13) , alcohol consumption (14) , contaminated food (12) , untreated water intake (5) , family size (15) , bed sharing (16) , poor living conditions in childhood (17) , educational (13) and socioeconomic level (18) , hygiene (19) , and family medical history of gastric disease (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Alebie et al (2016) in a study that included 145 Ethiopian students with gastritis found that consumption of coffee exacerbates H. pylori related gastritis symptoms [ 28 ]. Monno et al (2019) in a retrospective study conducted in Italy revealed that the frequent consumption of coffee increases the H. pylori infection rate [ 18 ], while other studies did not find any association between coffee consumption and H. pylori infection [ 10 , 29 , 30 ]. The relationship between coffee consumption and H. pylori infection might be attributed to the differences in the type of coffee consumed and preparation methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that frequent consumption of coffee was associated with an increased rate of H. pylori infection and exacerbation of H. pylori -related gastritis symptoms [ 18 , 28 ]. Some studies did not find any association between coffee consumption and H. pylori infection [ 10 , 29 , 30 ]. In addition, the relationship between H. pylori infection and several modifiable cardio-metabolic risk factors was reported in the literature [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%